Static and Dynamic Properties and Temperature Sensitivity of Emulsified Asphalt Concrete - Bin Huang; Yuting Zhang; Tian Qi; Hongxing Han (Advances in Materials Science and Engineering)
Asphalt concrete is a typical rheological material, which is hard brittle at low temperature and reflects soft plastic facture at high temperature; the temperature has a great influence on the mechanical properties of asphalt concrete. In order to eliminate the environmental pollution caused by hot asphalt construction, cationic emulsified asphalt can be used. This paper transforms the temperature control system for static and dynamic triaxial test equipment, which has achieved static and dynamic properties of emulsified asphalt concrete under different temperatures, and researched the temperature sensitivity of emulsified asphalt concrete materials including static stress-strain relationship, static strength, dynamic modulus of elasticity, damping ratio, and so on. The results suggest that (1) temperature has a great influence on the triaxial stress-strain relationship curve of the asphalt concrete. The lower the temperature, the greater the initial tangent modulus of asphalt concrete and the higher the intensity; the more obvious the softening trend, the smaller the failure strain of the specimen and the more obvious the extent of shear dilatancy. When the temperature is below 15.4°C, the temperature sensitivity of the modulus and strength is stronger significantly. (2) With the temperature rising, the asphalt concrete gradually shifts from an elastic state to a viscoelastic state, the dynamic modulus gradually reduces, and the damping ratio increases. When the temperature is above 15.4°C, the temperature sensitivity is obviously stronger for the dynamic elastic modulus and damping ratio. (3) The static and dynamic properties of asphalt concrete are very sensitive to the temperature. The test temperature should be made clear for the static and dynamic tests of asphalt concrete. The specimen temperature and the test ambient temperature must be strictly controlled.